Customers’ Experiences of Compassion and Brand Attitude: Evidence From Low-Cost Carriers - Ko, Sung-Hoon; Choi, Yongjun; Kim, Jongsung (Frontiers in Psychology, 2021)
The purpose of this study is to examine the effect of compassion experienced by low-cost carriers customers on their brand attitudes. Specifically, this study aims to unbox the mechanisms through how the customers’ experiences of compassion influence the formation of positive brand attitudes. Using the data from 423 low-cost carriers customers in South Korea, this study found that the more low-cost carriers’ customers experience compassion, the more positive their brand attitudes are toward the low-cost carriers. Notably, this study demonstrated that the positive relationship between compassion and brand attitudes is serially mediated by positive emotion and positive brand image. The results from this study contribute to the literature on the airline industry by examining the roles of compassion, which is relatively new to the field, and also provides practical insights for a low-cost carrier to come up with competitive strategies to achieve a competitive advantage over its competitors in the industry.